Depth/age model of sediment core MD99-2323 - Andrews, John T (PANGAEA, 2021)
Age model based on calibrated radiocarbon dates, tephra and paleomagnetic excursion age estimates (doi:10.1594/PANGAEA.936453) using the Baysian depth/age model “Bacon.”
Keywords: Depth/age; Snorri Drift